FACTORS ASSOCIATED WITH CHRONIC KIDNEY DISEASE AMONG PATIENTS UNDERGOING HEMODIALYSIS - Tjang, Yanto Sandy; Pandelaki, Paulus Anung Anindita (Majalah Kedokteran Indonesia, 2018)
Introduction: The development of chronic kidney disease (CKD) and later proportion of decline in renal function are diverse among individuals. This reflects the multifactorial biological mechanisms that are involved in the underlying disease process. The risk factors and resources for care of CKD also vary from place to place. Identifying the risk factors of CKD is crucial and develop prevention strategies, including screening, might be beneficial to reduce burden cost, morbidity and mortality of CKD. We aim at identifying the factors associated with CKD in individuals who have undergone hemodialysis. Material and Methods: All adult patients (age >18 years) admitted to the department of internal medicine either as in- or out-patient for undergoing hemodialysis at the Mardi Rahayu Hospital in Kudus, Middle Java, Indonesia from January to August 2016 were included in the study. Results: Eighty-two patients were evaluated during the study period. Most of the patients were in older age (> 50 years old). Sixty (73%) were male and 22 (27%) were female patients. Fifty (61%) patients had mild anemia, 23 (28%) patients had moderate anemia and 8 (10%) patients had severe anemia. Among 82 patients, 77 (94%) of the patients were hypertensive, 19 (23%) of the patients had DM, 23 (28%) of the patients had renal stone, 8 (10%) of the patients had renal cysts, and 7 (9%) of the patients suffered from glomerulonephritis. Conclusion: Older age, male gender, anemia, and hypertension were factors that associated with CKD among patients undergoing hemodialysis. Keywords: chronic kidney disease, risk factors, hemodialysis, anemia, hypertension